The Initial Development of Integrated Add-On Tele-Ultrasonography for Monitoring the Health of Pregnant Women and Fetuses in the Community Health Centers in Indonesia: - - Susanti, Hesty; Setiyadi, Suto; Puspitasari, Dita; Alia, Fenty; Ramadhan, Muhammad Rizqi Syah (Journal of Engineering and Technological Sciences, 2025)
Maternal health and fetal growth in rural areas require special attention due to limited access to adequate healthcare systems. Early detection of fetal health conditions can be achieved using B-mode ultrasonography (USG). However, expectant mothers in these regions often lack regular to regular check-up, even when healthcare facilities are available there may not be trained professionals available to analyze the B-mode images obtained in the Community Health Centres. To address this gap, a tele-USG system was developed that allows healthcare workers in remote areas to operate basic USG equipment and transmit real-time images to specialist doctors at higher-level healthcare facilities. During system development, a general-purpose USG phantom was used to test parameters: penetration depth, geometric accuracy, focal zone, and axial and lateral resolution. Testing confirmed that both USG and laptop used for streaming produce reliable and accurate results. A slight geometric representation differences of 2.74% (approximately 1 cm per target) was observed, attributed to dimensional distortion between devices with different monitor sizes. In geometric accuracy tests, five out of eight vertical and six out of seven horizontal targets were successfully detected. The smallest variation of 0.028 mm occurred at 5 MHz frequency, demonstrated high precision focal zone measurements. The axial resolution ranged between 0.25-0.5 mm, while lateral resolution ranged from 1.0-2.0 mm, indicating strong capability for fine-detail imaging. Overall, the system exhibited high sensitivity and excellent imaging performance, offering a promising solution to enhance maternal and fetal healthcare challenges faced by rural communities in Indonesia through accessible real-time diagnostic support